2021
DOI: 10.3390/gels7030103
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Copper(II), Cobalt(II) and Iron(III) Sorption in Binary and Ternary Systems by Chitosan-Based Composite Sponges Obtained by Ice-Segregation Approach

Abstract: With the intensive industrial activity worldwide, water pollution by heavy metal ions (HMIs) has become a serious issue that requires strict and careful monitoring, as they are extremely toxic and can cause serious hazards to the environment and human health. Thus, the effective and efficient removal of HMIs still remains a challenge that needs to be solved. In this context, copper(II), cobalt(II) and iron(III) sorption by chitosan (CS)-based composite sponges was systematically investigated in binary and tern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Preparation of graphene oxide/chitosan (GO/CS) composites as new promising sorbent materials for removal of heavy metal ions, dyes and other organic molecules from aquatic environment is presented in paper [ 169 , 170 ]. Sorption of copper (II), cobalt (II) and iron (III) ions, using chitosan composite sponges prepared by ice-segregation procedure, was studied for purification of waste water [ 171 ]. It has been determined that iron (III) ions were mainly adsorbed from two-component mixtures with cobalt (II) ions at pH = 4, whereas copper (II) ions were removed from two-component mixtures with cobalt (II) ions at pH = 6.…”
Section: Recent Researches Of Chitosan Biopolymersmentioning
confidence: 99%
“…Preparation of graphene oxide/chitosan (GO/CS) composites as new promising sorbent materials for removal of heavy metal ions, dyes and other organic molecules from aquatic environment is presented in paper [ 169 , 170 ]. Sorption of copper (II), cobalt (II) and iron (III) ions, using chitosan composite sponges prepared by ice-segregation procedure, was studied for purification of waste water [ 171 ]. It has been determined that iron (III) ions were mainly adsorbed from two-component mixtures with cobalt (II) ions at pH = 4, whereas copper (II) ions were removed from two-component mixtures with cobalt (II) ions at pH = 6.…”
Section: Recent Researches Of Chitosan Biopolymersmentioning
confidence: 99%
“…This behavior was associated with the existence of pre-organized recognition sites along with a highly interconnected porous morphology within the sorbents structure. Furthermore, as the industrial wastewater comprise mixtures of a broader variety of heavy metal ions, our group also evaluated the adsorption capacity of CS/CPL composite sorbents for Cu(II) ions from ternary or five-component synthetic mixtures with Zn(II), Ni(II), Fe(III), and Cr(III) ions [ 171 , 172 , 173 ]. It was shown that the removal efficiency of HMIs from their aqueous mixtures strongly depended on several characteristic parameters of the aqueous media, such as the presence of other contaminants or competing species, ionic strength, temperature, and pH [ 171 , 172 , 173 ].…”
Section: Polysaccharide-based Composite Hydrogels Applied In Wastewat...mentioning
confidence: 99%
“…Furthermore, as the industrial wastewater comprise mixtures of a broader variety of heavy metal ions, our group also evaluated the adsorption capacity of CS/CPL composite sorbents for Cu(II) ions from ternary or five-component synthetic mixtures with Zn(II), Ni(II), Fe(III), and Cr(III) ions [ 171 , 172 , 173 ]. It was shown that the removal efficiency of HMIs from their aqueous mixtures strongly depended on several characteristic parameters of the aqueous media, such as the presence of other contaminants or competing species, ionic strength, temperature, and pH [ 171 , 172 , 173 ]. The overall sorption tendency of CS/CPL sorbents toward Cu(II) ions in the presence of Zn(II), Ni(II), Fe(III), and Cr(III) ions, under competitive conditions, followed the order: Cu(II) > Fe(III) > Ni(II) > Zn(II) > Cr(III) with distribution coefficients values of 4.23, 2.74, 1.43, and 55.9.…”
Section: Polysaccharide-based Composite Hydrogels Applied In Wastewat...mentioning
confidence: 99%
“…In line with this requirement, eco-materials based on biopolymers, able to detect and recover heavy metals, constituted the base of new materials designed to detect or recover mercury. Cellulose-, lignin-, chitosan-, or peptide-based hydrogels/xerogels proved to have a high ability to bond mercury, encouraging their deeper consideration, in order to create high-performance adsorbent materials [ 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. It was established that polysaccharides are excellent sorbents for heavy metals thanks to their ability to develop physical and electrostatic forces, which can be further improved by grafting moieties capable of coordinating metals.…”
Section: Introductionmentioning
confidence: 99%